المسائل الفقهية التي خالف فيها ابن العربي مشهور مذهب المالكية جمعًا ودراسةً _الحج والصوم الزكاة أنموذجًا_ - عبد الرؤوف, قسوم (University of Eloued جامعة الوادي, 2019)
"هاته الدّراسة بعنوان: ""المسائل الّتي خالف فيها ابن العربي مشهور مذهب المالكيّة جمعًا ودراسة _الحج والصّيام والزّكاة أنموذجًا_"" كان إشكالها الرّئيس الذي تحاول الإجابة عنه هو: ماهي المسائل الّتي خالف فيها ابن العربي مشهور المالكيّة في أبواب الحجّ والصّوم والزّكاة؟ وما مستنده في ذلك؟ أجابت الدّراسة على ذلك من خلال مبحث تمهيدي، ومبحثين تطبيقيّين، خُصِّص المبحث التّمهيدي لترجمة الإمام ابن العربي مع تعريجٍ موجزٍ لمعنى الحجّ والصّوم والزّكاة؛ مفهومًا وأركانًا وسننًا وغيرها، إضافةً إلى بيان لمعنيي المشهور والمخالفة، ثم أُفرِد المبحث الأوّل للمسائل التي خالف فيه ابن العربي مشهور مذهب المالكيّة في باب الصّيام، لِتُختَم الدّراسة بالمبحث الثّاني الذي عُني ببيان مسائل الحجّ والزّكاة. وتوصّلت الدّراسة لجُملة من النّتائج، لعلّ أهمّها هو أن الانتساب الصحيح للمذهب المالكي عند ابن العربي، هو انتساب أصول وقواعد لا مجرد الجمود على القول المشهور فقط، الأمر الذي حمله على عدم الجنوح للتّقليد المذهبيّ، بل كان فقيهًا مجتهدًا متحررًا، وهو ما جعله يخالف المالكيّة في بعض مشهور ما ذهبوا إليه، حيث بلغ عدد المسائل الّتي خالفهم فيها في هذا البحث: سبع عشرة مسألة، كان أكثرها في باب الصّيام وأقلّها في باب الزّكاة، ولعلّ أشهر المسائل التي خالف فيها مشهور مذهب المالكيّة؛ مسألة زكاة الخُضروات، التي حُظيت هي وغيرها بدراسةٍ وتمحيصٍ لمستند المخالفة، مع ذكر لبعض أسباب الخِلاف في ذلك. " "This study is entitled ""The subjects which IBN-ALRABI disagrees with the most common rules of the MALKIAN school _ Hajj، Siam، and Zakkah as samples_"". The main problems of this study which tryies to answer are: what are the subjects which IBN-ALRABI disagrees with the most common rule of the MALKIAN school? And what are his references? This study answered that through a preliminary part and tow parts of Applid studies. The preliminary study deals with introducing the scholar IBN-ALRABI، and the definition of: Hajj، Siam، and Zakkah; focusing on its conceptual and pillard phases. In addition، it deals with the tow concepts of Doctrine and Disagreement. The first part of the study deals with the issues that IBN-ALRABI disagreed concerning Siam. Finally، the study ends with the issues of Hajj and Zakkah. This study comes up with many results، the most important of them is: According to IBN-ALRABI the right belonging to MALKIAN doctrine is to belong to fundementals and rules، not only being enough of the doctrinal tradition; but he was free and steady scholar that's why he disagrees with MALKIAN in some issues. IBN-ALRABI disagrees in seventeen issues in this study. The majority of it was in Siam، and the least of it was Zakkah. The most known subject that IBN-ALRABI disagreement with MALKIAN was about the Zakkah of vegetables which got_ and others- a particular study based on Disagreement; mentioning many causes of the disagreement. "
مذكرة ماستر تخصص فقه مقارن
Keywords: ابن العربي _ المشهور _ المالكية; IBN ALRABI - FAMOUS- ELMALIKIA